Effect of instantaneous light intensity after magnesium suppression in tomato and bell pepper cultivation - Lisboa, Lucas Aparecido Manzani [UNESP] (2024)
Plants dynamically respond to varying light intensities, which may further interact with their nutrient status to affect gas exchange parameters. This study investigated the combined effect of instantaneous light intensity and magnesium suppression on tomato and bell pepper cultivation. Two independent experiments were conducted in September 2022 using the tomato variety Mariana (Sakata®) and bell pepper variety Magali R (Sakata®) at the Faculty of Agricultural and Technological Sciences, Dracena, São Paulo, Brazil. A completely randomized 2x5 factorial design was employed, with the first factor being the presence/absence of magnesium in the nutrient solution and the second factor being four light intensities: 0 (control), 600, 1200, and 1800 μmol m-2 s-1 photosynthetically active radiation (PAR) applied instantaneously using an IRGA device. Magnesium deficiency was confirmed to be a limiting factor for gas exchange responses in both tomato and pepper crops. Notably, the light intensity of 1200 μmol m-2 s-1 PAR elicited the most optimal gas exchange performance in both plant species.